Theoretical foundations of the problem of mentoring. - Byhar, Hana; Kozyar, Mykhailo (Pedagogy and Education Management Review, 2022)
The article considers the peculiarities of mentoring and preparation for its implementation in higher education institutions. The purpose of the article is to study the possibilities of mentoring in the learning process in higher education institutions. The following methods were used: theoretical - analysis of scientific literature, legal documents, curricula, synthesis, classification, generalization, comparison and systematization of data to study the state of the research problem; empirical - questionnaires, surveys, interviews, in order to study the state of readiness of future professionals for mentoring; methods of Mathematical Statistics - using Pearson's consistency criterion for quantitative and qualitative processing of experimental data, proving the reliability of the obtained research results. The urgency of the problem related to the process of education is shown. For young professionals, the basis of the education system is mentoring, which is the main form of establishing personal relationships between team members. Scientists have determined the place of the mentor in the system of education of beginners. It is determined that the main factor of professional development of a specialist is individual professional position. It is proved that preparation for mentoring is characterized by a number of specific terms: "mentor", "mentoring", "readiness of future professionals for mentoring". This process must meet certain requirements for the mentor: general erudition, professional intuition, intellectual abilities, general culture and morality, professional mastery of specific methods of education. The qualities that characterize the mentor are studied. These include: corporate culture; practical training; understanding of personal responsibility; purposefulness; vision of the end result; formed motivation; being an authoritative person; possession of leadership skills. Professional competence is prioritized by scientists. The ways of influence of the mentor on students / cadets were chosen: focus of activity on achievement of success; joint participation in solving unforeseen situations; organization of events using effective measures; own example. There are several types of mentoring: tutoring, coaching, mentoring, research guidance, supervision. All these types are characterized by individualization of the educational process. Insufficient study of the problem of mentoring has been identified.
Keywords: Keywords: mentoring, mentor, future specialists, the main qualities of a mentor, requirements for mentoring, ways to implement mentoring